PENGEMBANGAN CATU DAYA PRESISI DISPLAY DIGITAL UNTUK PRAKTIKUM FISIKA LISTRIK DINAMIS - Hamid, Bushra; Agustiyanto, Frans Rizal; Yulkifli, Yulkifli (Sainstek : Jurnal Sains dan Teknologi, 2016)
This study aims to generate power supply precision instrument digital display a valid and practical for students of physics 3rd semester of the school year 2014/2015. This research includes development research (research development) of the power supply circuit that has been common there are some drawbacks, namely, the output of output that does not fit, there is still AC voltage on the output value, the output voltage is unstable, so that the results of the lab basic physics 2 be not in accordance with the results of the theory. The addition of the diode bridge circuit helps perfect output voltage into DC, the capacitors in the circuit capacity was raised as a reliever ripple or ripples form to obtain a stable DC voltage value, for a voltage stabilizer is also used IC9815 surge protector. Limited trial conducted in STAIN Batusangakar to 26 students. Based on the results of data analysis has been carried out can be summarized as follows: (1) The results of the validation tool precision power supply digital display is very valid. (2) The results of trials carried out showed that the practicalities have met the criteria that can be used and implemented in a lab with practicality very practical value.